Taxonomic significance of petal and sepal micromorphological characteristics in some justicia nees (Acanthaceae) species in Peninsular Malaysia - Ahmad Juhari, Muhammad Amirul Aiman; Talip, Noraini; Che Amri, Che Nurul Aini; Abdul razak, Siti Khaulah; Mansur, Nurul-Syahirah; Rushdi, Amalia; Abdul Rahman, Ruzi (Penerbit Universiti Sains Malaysia, 2019)
Acanthaceae is a flowering plants family under the order Lamiales and comprises at least 4,000 species regardless of tropical and subtropical species with Justicia being the largest genus under this family. The study on the flower’s petal and sepal micromorphology have been done on six Justicia species, namely as Justicia betonica L., J. carnea Lindl., J. comata (L.) Lam., J. gendarussa Burm.f., J. procumbens L. and J. ptychostoma Nees. Methodology used involves fixation, dehydration series, critical point drying technique and observation under scanning electron microscope. Results have shown that all six species have differences in micromorphological characteristics in the sepals and petals epidermal surfaces. Cuticular wax can be found on both abaxial and adaxial epidermal surfaces of petal and sepal for all species studied. Granular cuticular wax is the only type of cuticular wax was found present on petal and sepal of all species studied. There are also eight types of trichomes present on the petal epidermal surface and eight types of trichomes present on the sepal epidermal surface. J. betonica can be recognised directly by having amphidiacytic stomata on petal epidermal surface while stomata were absent on the petal epidermal surface of other species. As a conclusion, findings in this study have proven that petal and sepal micromorphological characteristics have systematic significant and can be used as supporting data for species differentiation and identification in the genus Justicia.